The Effects of Resiliency on University Students’ Happiness and Life Effectiveness amid the COVID-19 Pandemic Religious Faith Stands as a Moderator - Getrude C. Ah Gang @ Grace; Gussago, Luigi; Chua, Bee Seok; Carmella E. Ading (Common Ground Research Networks, 2022)
It is argued that resiliency may contribute to one’s happiness and life effectiveness, while religious faith may strengthen the effects arising from the interchange of those variables. To confirm these assumptions, a study was conducted on a group of students consisting of 506 public and private university students in Sabah, Malaysia, amid the COVID-19 pandemic. Of the participants, 405 (80%) were females, 100 were males (19.8%), and one did not reveal their gender. The mean age was 21.71 (SD = 4.52). The study revealed that resiliency accounted for 6 percent of the variance on happiness and 18 percent of the variance on life effectiveness. However, faith did not show any moderation effects on resiliency as a cause of happiness. In terms of its effect on students’ life efficiency (e.g., time management, emotional control, and social competence), resiliency accounts for 18 percent of the variance on life effectiveness. As to the interaction between resiliency and faith in relation to the quality of life, the study revealed a significant interaction between them, a result that explained an additional 1.6 percent in the variance in life effectiveness. This indicates that strong religious faith could enhance students’ resiliency and contribute to a better life (e.g., managing time, controlling emotion, higher motivation, and competence in social situations), particularly during the pandemic. Therefore, valuing and practicing one’s religious faith, regardless of the religious background, is a powerful tool in boosting students’ flexibility in the face of academic and nonacademic challenges during the COVID-19 pandemic.